Serological evidence of exposure to a coronavirus antigenically related to severe acute respiratory syndrome virus (SARS‐CoV‐1) in the Grey‐headed flying fox (Pteropus poliocephalus). Issue 4 (26th November 2020) - Boardman, Wayne S. J.; Baker, Michelle L.; Boyd, Victoria; Crameri, Gary; Peck, Grantley R.; Reardon, Terry; Smith, Ian G.; Caraguel, Charles G. B.; Prowse, Thomas A. A.
Abstract: Many infectious pathogens can be transmitted by highly mobile species, like bats that can act as reservoir hosts for viruses such as henipaviruses, lyssaviruses and coronaviruses. In this study, we investigated the seroepidemiology of protein antigens to Severe acute respiratory syndrome virus (SARS‐CoV‐1) and Middle eastern respiratory syndrome virus (MERS‐CoV) in Grey‐headed flying foxes ( Pteropus poliocephalus ) in Adelaide, Australia sampled between September 2015 and February 2018. A total of 301 serum samples were collected and evaluated using a multiplex Luminex binding assay, and median fluorescence intensity thresholds were determined using finite‐mixture modelling. We found evidence of antibodies reactive to SARS‐CoV‐1 or a related antigen with 42.5% (CI: 34.3%–51.2%) seroprevalence but insufficient evidence of reactivity to MERS‐CoV antigen. This study provides evidence that the Grey‐headed flying foxes sampled in Adelaide have been exposed to a SARS‐like coronavirus.